The nonclassicality of a quantum system in weak measurement by means of modular values. Issue 5 (12th March 2021) - Rafiepoor, E.; Bazrafkan, M. R.; Batebi, S.
Abstract : Using Bochner's theorem, we derive a necessary and sufficient hierarchy of measurable conditions in terms of the characteristic function of quasi-moments of a weakly measured observable. A quantum system that violates any of these conditions is nonclassical in weak measurements. Then, we formulate nonclassicality conditions obtained in terms of modular values that can be easily measured by performing a tomography of the final state of a qubit device. This method provides us direct access to the characteristic function as the generating function of quasi moments of weakly measured observable. In this way, We solve the problem of experimental restrictions on measuring the infinite number of weak quasi-moments.